Living with a loved one’s mental health issue: Recognizing the Lived Experiences of Military Spouses - Senior, Emma; Clarke, Amanda; Wilson-Menzfeld, Gemma (PLOS ONE, 2025)
Limited evidence surrounds the lived experiences of military spouses whose partner has mental health issues. This lack of evidence may be due to factors such as global austerity, underfunding of armed forces, and inadequate healthcare systems. As a result, family members—especially spouses—often end up being the primary caregivers for their military partners with mental health issues. The study used a qualitative, biographical methodology, collecting data through life stories. Two face-to-face semi-structured interviews took place with nine military spouse recruited through military spouse networks and snowballing. Lieblich et al.’s (1998) framework provided analytical pluralism, which allowed for both narrative and thematic analysis. Stories are presented in the stages ‘in the beginning’, changing times’ and ‘this is me’. Thematic analysis identified six overarching categories; Living with disruption, living in the midst of it all, It isn’t enough, seeking support, Diagnosis and treatment, Living alongside. Whilst the first of its kind in the UK, this biographical study advances both national and global understanding of military spouse experiences in the context of mental health. Both the stories and the categories indicate that living with a serving partner who has mental health issues is a complex journey marked by both struggle and growth. A uniqueness arising from this study highlights the period leading up to a mental health diagnosis, emphasising the prolonged emotional and psychological strain experienced by military spouses before any formal recognition of mental illness in their serving partner. The study adds a new dimension to understanding the emotional toll on military spouses and underscores the importance of early recognition and support. While participants faced emotional detachment and feelings of invisibility, they also identified gains in resilience and strengthened relationships. Through the convergence of the narrative and thematic analysis the participants experience throughout their partners mental health issue is conceptualised in a Relationship Trajectory model. It illustrates the positive, early relational strength, superseded by relationship decline followed with relationship reinvention.